Grain size characteristics of different types of surface sediments around Qixing Lake in Kubuqi Desert - Xi, Cheng; Zuo, Hejun; Yan, Min; Yan, Yu (Frontiers in Environmental Science, 2024)
Sediment grain size characterization is one of the main components of aeolian geomorphology research. Sand particle size can determine the basic form of sand movement. The distribution and form of grain size parameters of different types of sediments were calculated using six surface types of sediments around Qixing Lake in the Kubuqi Desert: Mobile dune Semi-fixed dune Fixed dune Lakeshore terrace Wetland and Grassy flat wetland The results showed that the surface sediments were mainly composed of medium sand and fine sand, and all types were negatively skewed. The differentiation pattern of the saltation component and suspended component of the surface sediment is characterized by a two-stage pattern. The percentage contribution of suspended components in lakeshore terraces, wetlands, and Grassy flat wetlands (total average 21.07%) is more than twice that of mobile dunes, semifixed dunes, and fixed dunes (total average 9.47%). This suggests that mobile dunes, semi-fixed dunes, and fixed dunes are not the main contributing surface type of suspended material in the Qixing Lake area.